EVENTRATION OF DIAPHRAGM IN ADULTS: ELEVEN YEARS EXPERIENCE - Shah, Syed Zahid Ali; Khan, Shahbaz Ali; Bilal, Amir; Ahmad, Manzoor; Muhammad, Gul; Khan, Khalid; Khan, Muhammad Amjad (Journal of Ayub Medical College Abbottabad, 2014)
Background: Eventration of diaphragm is a congenital condition in which there is absence of muscle fibers in the diaphragm while maintaining all the anatomical attachments normally. Surgical treatment is warranted in symptomatic patients so as to reduce the abnormal ascent of diaphragm. The present study was conducted to analyse the perioperative outcome of thoracotomy in adult patients with diaphragmatic eventration. Methods: This descriptive case series was carried out in Cardiothoracic Surgery-Unit, Postgraduate Medical Institute, Lady Reading Hospital, Peshawar, Pakistan. Medical records of patients operated upon for eventration from June 2002 to June 2013 were reviewed. Patients of either gender, above 16 years who were operated for symptomatic eventrtaion were included in study. All the demographic data, presenting complaints, baseline and post-postoperative dyspnea grade, forced expiratory volume at 1 second (FEV1) and forced vital capacity (FVC) were recorded on predesigned pro forma and analysed using SPSS-16. Results: A total of 38 adult patients underwent surgery for diaphragmatic eventration over the past 11 years in our unit out of which 29 (76%) were males and rest of 9 (24%) were females. Mean age of patients was 41.6±13.84 years. In 31 (81.5%) patients left side was involved. Majority of patients had a dyspnea grade-3 on presentation. Preoperative dyspnoea score (MRC), FEV1 and FVC values were 2.6±0.73, 63.5±13.3 and 67.2±14.6 respectively. Pre-operative and 6-months follow-up values of dyspnoea grade, FEV1 and FVC values showed statistically significant improvement. Conclusion: Our study showed that adult patients with symptomatic unilateral eventration of diaphragm significantly benefit from diaphragmmatic plication. Keywords: Eventration, diaphragm, thoracotomy, Dyspnea score, FEV1, FVC